Environmental Graphic In Safavi Era - Ourangi, Zahra (The Turkish Online Journal of Design Art and Communication, 2016)
Environmental graphic art emerged in Europe and America in order to organize buildings, streets and create serenity and facilitate human movement and create beauty. Iranian artists and graphists consider this branch of graphic art as a newly appeared event and consider its origins in the industrial revolution. Dealing with environmental graphic of Iran which is one of the branches of Graphic in the present era and its relationship with humanitarian and social sciences such as urbanism, communications, sociology, psychology, architecture, etc in the light of sacred Islam is highly significant. The most principle function of environmental graphic is to allot indigenous identity to the surrounding environment in terms of visual originality. Identifying and introducing an apposite pattern in this respect is very essential. Therefore two questions are raised: Is there a historic background of the modern environmental graphic art in different areas at the time of Safavi or not? Is it possible to borrow apposite pattern from the remaining works of Safavi era to solve the problem of the lack of Iranian-Islamic-Shia? The results of the present study are the emergence of deep thinking of human and the appearance of special spirituality identity of Shia Islam that employs descriptive, analytic methodology and by the adaptation of the remaining images of the Safavi era refers to the appearance of environmental graphic art in modern fields before twenty first century and introduces a unique sample of artistic return to the contemporary graphic artists. A thought and idea, whose absence in the mind of graphists, architects and city planners can be seen.
Keywords: environmental graphic; modern pattern of Iranian-Islamic-Shia; Safavi dynasty; modern era